2014
DOI: 10.3389/fnhum.2014.00993
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the rehabilitation of memory post acquired brain injury: a systematic review

Abstract: Objective: Acquired Brain Injury (ABI) frequently results in memory impairment causing significant disabilities in daily life and is therefore a critical target for cognitive rehabilitation. Current understanding of brain plasticity has led to novel insights in remediation-oriented approaches for the rehabilitation of memory deficits. We will describe 3 of these approaches that have emerged in the last decade: Virtual Reality (VR) training, Computer-Based Cognitive Retraining (CBCR) and Non-Invasive Brain Stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 49 publications
0
40
0
5
Order By: Relevance
“…Memory functions have a place in the model because memory is critical to language processing and production (171). Memory impairments are common after ABI with reported incidence rates from 20% to 79% depending on aetiology, severity, and time post injury (172). They may involve episodic, declarative, or prospective memory and have been found to affect communication functions such as auditory comprehension, reading comprehension, verbal expression and discourse, written expression, or social communication (76,78,89,154,170,173,174).…”
Section: Memorymentioning
confidence: 99%
“…Memory functions have a place in the model because memory is critical to language processing and production (171). Memory impairments are common after ABI with reported incidence rates from 20% to 79% depending on aetiology, severity, and time post injury (172). They may involve episodic, declarative, or prospective memory and have been found to affect communication functions such as auditory comprehension, reading comprehension, verbal expression and discourse, written expression, or social communication (76,78,89,154,170,173,174).…”
Section: Memorymentioning
confidence: 99%
“…Когнитивные тренировки могут способствовать восстановлению памяти [58] за счет улучшения кодирования и поиска информации, в частности, путем вовлечения сохранных участков мозга, отличающихся от тех, что ранее использовались для кодирования информации [56]. Например, зрительная информация может использоваться для улучшения кодирования вербальной информации или способствовать ее сохранению и извлечению [5].…”
Section: когнитивные тренировки и нейрореабилитацияunclassified
“…Подавляющее большинство выживших новых клеток дифференцируются в нейроны и способны формировать синапсы и генерировать потенциалы действия, включаясь в существующую структурную и функциональную схему взрослого мозга. В систематическом обзоре [58] выполнен критический анализ результатов исследований по реабилитации пациентов с приобретенным травматическим повреждением головного мозга с помощью методов, основанных на виртуальной реальности, компьютерной когнитивной «пере-подготовки» и неинвазивной стимуляции мозга (НИСМ). Результаты исследований поддерживают компьютерную когнитивную тренировку как эффективный метод улучшения рабочей памяти после ЧМТ [5].…”
Section: когнитивные тренировки и нейрореабилитацияunclassified
See 1 more Smart Citation
“…Evidence supporting the efficacy of restoration of memory functioning in individuals following TBI is still sparse but growing [18]. In 2007, Thick penny-Davis and Barker-Collo [19] found that an 8 session memory treatment intervention involving internal and external memory strategies greatly improved participants standardized memory test performance, and increased their knowledge of memory.…”
Section: External Versus Internal Strategiesmentioning
confidence: 99%